Household Water Treatment Practice and Associated Factors in Rural Households of Sodo Zuria District, Southern Ethiopia: Community-Based Cross-Sectional Study - Amha Admasie; Kefelegn Abera; Fentaw Wassie Feleke (SAGE Publishing, 2022)
Introduction: In Ethiopia, access to safe drinking water is very low, and even safe water at the point of distribution is subjected to frequent and substantial contamination during collection, transport, and storage. The purpose of this study was to assess the level of household water treatment practices and associated factors in rural households of the Sodo Zuria district, southern Ethiopia. Methods: A community-based cross-sectional study was conducted in 836 households using a multistage sampling technique. A structured and pre-tested questionnaire was used. Binary and multivariate logistic regression analysis was used. Results: The household water treatment practice was 44.1%. Households having a higher estimated monthly income, AOR = 1.5 (1.23, 3.47), older age greater than 45 years, AOR = 1.69 (1.08, 2.64), fetching water twice a day, AOR = 2.8 (1.21, 9.17), weekly washing of the water storage container, AOR = 0.3 (0.11, 0.83), and using the dipping technique to draw water from the collection jar, AOR = 1.67 (1.14, 2.42) were significant factors in the practice of household water treatment in the study. Conclusions: The household water treatment practice was low. Higher estimated monthly income, older household heads, fetching water twice per day, washing the water storage container weekly, and dipping techniques to draw water from water storage containers were significant factors of household water treatment practices. Thus, proper hygiene of water storage, and engaging the community in income-generating activities were recommended.